2017
DOI: 10.1016/j.watres.2016.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cation valance and exchange on the retention and colloid-facilitated transport of functionalized multi-walled carbon nanotubes in a natural soil

Abstract: a b s t r a c tSaturated soil column experiments were conducted to investigate the transport, retention, and release behavior of a low concentration (1 mg L À1 ) of functionalized 14 C-labeled multi-walled carbon nanotubes (MWCNTs) in a natural soil under various solution chemistries. Breakthrough curves (BTCs) for MWCNTS exhibited greater amounts of retardation and retention with increasing solution ionic strength (IS) or in the presence of Ca 2þ in comparison to K þ , and retention profiles (RPs) for MWCNTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 57 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…4) can be related to higher EC (Table 2) and greater divalent cations (data not shown) in ZR soil. Similarly Zhang et al (2017) reported more retention of MWCNT in the presence of Ca 2+ compared with K + ions. They also observed that in the presence of Ca 2+ , the blocking behavior enhanced and RPs exhibited a hyperexponential shape.…”
Section: Transport and Retention Of Agnps Through Saturated And Unsatmentioning
confidence: 86%
“…4) can be related to higher EC (Table 2) and greater divalent cations (data not shown) in ZR soil. Similarly Zhang et al (2017) reported more retention of MWCNT in the presence of Ca 2+ compared with K + ions. They also observed that in the presence of Ca 2+ , the blocking behavior enhanced and RPs exhibited a hyperexponential shape.…”
Section: Transport and Retention Of Agnps Through Saturated And Unsatmentioning
confidence: 86%
“…It is reasonable to conclude that the ionic strength will affect the thickness of the double layer of the colloid surface [45,49,50]. Compared with monovalent cations, divalent cations in solutions were more favorable for the colloid deposition by increasing electrostatic attraction between the colloids and sand surfaces, causing the cation bridge [46,47,51]. Thus, the transport of reduced Ni 2+ may be because it involved the interaction between soil colloids and sand.…”
Section: Effect Of Ion Strengthmentioning
confidence: 99%
“…favorable for the colloid deposition by increasing electrostatic attraction between the colloids and sand surfaces, causing the cation bridge [46,47,51]. Thus, the transport of reduced Ni 2+ may be because it involved the interaction between soil colloids and sand.…”
Section: Effect Of Humic Acidmentioning
confidence: 99%
“…DLS is the most used tool for the size characterization of spherical particles, commercial equipments being available and widespread. In many cases, these commercial devices, prepared for spheres, are used for the size characterization of non-spherical particles in suspension 11 , 17 23 . However, it has been shown that, for these geometries, the contribution of rotational diffusion, not taken into account, can have important effects on the DLS determinations 24 , 25 , and hence alternative approaches must be proposed.…”
Section: Dls For Size Characterization Of Non-spherical Particlesmentioning
confidence: 99%